Answer:
It is 6 from what I believe.
What is the distance between (8,-3) and (4,-7)
Answer:
The distance between 8,-3 is 12 and the distance between 4,-7 is 11
Step-by-step explanation:
solve -5 ( 1-4a) > -5
Answer:
A=0
Step-by-step explanation:
i think this is right if not im so sorry
Find the derivative of y = 2(x^2) - x + 4 at x = 2
Answer:
7.
Step-by-step explanation:
y = 2x^2 - x + 4
The derivative y' = 2*2x^(2-1) - 1
= 4x - 1
At x = 2 y' = 4(2) - 1 = 7.
Answer:
7
Step-by-step explanation:
Differentiate using the power rule
[tex]\frac{d}{dx}[/tex](a[tex]x^{n}[/tex]) = na[tex]x^{n-1}[/tex]
Given
y = 2x² - x + 4, then
[tex]\frac{dy}{dx}[/tex] = (2 × 2)x - 1 = 4x - 1
At x = 2 ⇒ [tex]\frac{dy}{dx}[/tex] = (4 × 2) - 1 = 8 - 1 = 7
The distance between the two islands showed on the map is 210 miles a ruler measure distance on the map as 3 1/2 inches how many miles would be represented by 1 3/4 inches on the map
let's firstly convert the mixed fractions to improper fractions.
[tex]\bf \stackrel{mixed}{3\frac{1}{2}}\implies \cfrac{3\cdot 2+1}{2}\implies \stackrel{improper}{\cfrac{7}{2}}~\hfill \stackrel{mixed}{1\frac{3}{4}}\implies \cfrac{1\cdot 4+3}{4}\implies \stackrel{improper}{\cfrac{7}{4}} \\\\[-0.35em] ~\dotfill\\\\ \begin{array}{ccll} \stackrel{size}{actual~miles}&\stackrel{size}{map~inches}\\ \cline{1-2} 210&\frac{7}{2}\\\\ x&\frac{7}{4} \end{array} \implies \cfrac{210}{x}=\cfrac{~~\frac{7}{2}~~}{\frac{7}{4}}[/tex]
[tex]\bf \cfrac{210}{x}=\cfrac{~~\begin{matrix} 7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} 2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\cdot \cfrac{\stackrel{2}{~~\begin{matrix} 4\\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{~~\begin{matrix} 7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~} \implies \cfrac{210}{x}=2\implies 210=2x\implies \cfrac{210}{2}=x\implies 105=x[/tex]
M angle 1 equals 4x + 15 + m angle 2 equals 2x + 16 what is angle 3 and what is X
Are you talking about the angles in a triangle? Your question is not clear. I'll assume you are talking about a triangle.
Angle 1 + Angle 2 + Angle 3 = 180°
4x + 15 + 2x + 16 + x = 180°
Solve for x to find Angle 3, which in this case is the value of x.
if the length of a side of a square is the square route of the area, what is the length of a side for each label?
Answer:
Area of a square = side times side. Since each side of a square is the same, it can simply be the length of one side squared. If a square has one side of 4 inches, the area would be 4 inches times 4 inches, or 16 square inches.
Step-by-step explanation:
CHALLENGE To find 1,188 divided by 12, I think about 1,200 divided hun
that's 100 groups of 12. 1,188 has 1 fewer group of 12.
Answer:
1188 divided by 12 is 99
Answer:
this is a hard one
Step-by-step explanation:
Solve the following equation. Then place the correct number in the box provided. 5x/8+10=2
Answer:
3 with a remaider of 2
Step-by-step explanation:
10+8=18 5/18=3 with a remainder of 2
5x/8+10=2
-10 each side of the equation
5x/8=-8
multiply each side by 8
5x=-64
divide each side by 5
And then you have your answer x=12 4/5
What is the change in temperature from -45°F to - 71°F?
1. 26°F
2. -116°F
3. 116°F
4. -26°F
Hey there you answer is -26°F Because, if you subtract -45 from -71 you would get -26 because it is still in the negative's place. Hope this helped! Your fellow Brainly user, GalaxyGamingKitty.
Determine whether each pair of triangles is congruent. If so, state whether they are congruent by
SSS, SAS, or ASA. If not, explain why.
Answer:
yes they're congruent.
The given information does not provide specific triangles or measurements needed to determine congruency, making it impossible to answer the question.
Explanation:The question asks about determining whether pairs of triangles are congruent and identifying the congruence criteria (SSS, SAS, ASA).
Unfortunately, the provided information does not include any pairs of triangles or any specific measurements needed to determine congruency.
Therefore, it is not possible to answer the question based on the given information.
2) According to Consumer Reports magazine, the costs per pound of protein for 20 major-brand beef hot dogs are
$14.23, $21.70, $14.49, $20.49, $14.47, $15.45, $25.25, $24.02, $18.86, $18.86, $30.65, $25.62, $8.12, $ 12.74,
$14.21, $13.39, $22.31, $19.95, $22.90, and $19.78, respectively. If the least expensive is considered the top-
ranked, what is the position in terms of a z-score of Thorn Apple Valley beef hot dogs at $14.23 per pound of
protein?
A) -2.67
B) -0.85
C) 0.85
D) 1.42
E) 2.67
Statistics: How would I find the answer?
Answer: -0.85
Step-by-step explanation: a = score-mean/ standard deviation
Mean (add them all up and divide by amount) = 18.8745
Standard deviation =
σ2 = Σ(xi - μ)2/N
= 5.333458985499
SCORE = 14.23
= -0.85
Calvina makes a car payment of $214.50 every month. Her car loan is for 5 years. How much will she pay in 5 years?
$12870 hope this helps bebe :)
What is the answer for this question
Answer:
6.3 kilograms
Step-by-step explanation:
Because 1 kilo is 2.2 pounds, divide 13.86 pounds by 2.2 to get 6.3 kilograms
Answer:
There are 6.3 Kilograms
Step-by-step explanation:
1 kilogram = 2.2 pounds
13.86 pounds = ? kilograms
[tex]\frac{13.86}{2.2} = 6.3[/tex]
Answer question 1 and 2 below and show your work.
Suzie and Devon had breakfast at a cafe. Muffins cost $4 on each, and fruit cups cost $7 each. Suzie had 2 muffins and 2 fruit cups. Devon had 3 muffins and 1 fruit cup. How much did their breakfast cost? Show work.
Tyler wants to ride the bumper cars 4 times and Ferris wheel 8 times. It costs 6 tickets to ride the bumper cars and 3 tickets to ride the Ferris wheel. How many tickets does tyler need? Show work.
Answer:
1st Part- $41 2nd Part- 48 Tickets
Step-by-step explanation:
1st Part)
Suzie- 2($4) + 2($7)= $22
Devon- 3($4)+ 1($7)= $19
Total=$41
-------------------------------------------------
2nd Part)
4(6) + 8(3) = 48 Tickets
Which of the following would be the most logical first step to solving this
quadratic equation?
x2 -5x + 6 = 0
Answer:
Step-by-step explanation:
There are many ways to solve this:
- factorising
- formula
- perfect squaring
FACTORISING:
The first step would be to multiple the coefficient of x^2 and 6.
Then find which of the factors of 6 sum up to 5. (In this case it is 2 and 3.)
So you would rewrite the equation like this:
x2 -3x -2x + 6 = 0
Then factorise
x(x-3) - 2(x-3) = 0
Then factorise again
(x-2)(x-3) = 0
So if we were to divide each side by (x-2)
(x-3) =0
so x = 3
OR
if we were to divide each side by (x-3)
(x-2) = 0
x = 2
FORMULA:
The formula is
-b±[tex]{\sqrt{b^2 -4ac}[/tex] / 2a
where
ax^2 + bx + c = 0
The first step would be to substitute.
PERFECT SQUARING:
The first step would be to half the second term.
[tex](x - \frac{5}{2})^{2} - \frac{25}{4} - 6 = 0[/tex]
Then solve for x.
Add or subtract.
7+3+ (-7)
17
3
-3
10
Answer:
3 is your answer
Step-by-step explanation:
What you do is PEMDAS
7 + 3 + (-7) You will add 7 and 3 together first.
10 + (-7) You will subtract 10 and -7
3 is your answer.
Which of the following statements is false?
If a number is a natural number, then it is rational.
If a number is a whole number, then it is rational.
If a number is a fraction, then it is rational.
If a number is an integer, then it is irrational. ( I think it could be this one but this rational number thing confuses me)
I will mark brainliest!
Answer: the false one is the last one (if a number is an integer, then it is irrational)
Step-by-step explanation:
Answer:
D is the correct answer.
Help!! Me with my aleks!
Answer:
9x + 36 = 10
Step-by-step explanation:
Given
[tex]\frac{3}{4}[/tex] x + 3 = [tex]\frac{5}{6}[/tex]
Multiply by the lowest common multiple of 4 and 6, that is 12
12 × [tex]\frac{3}{4}[/tex] x + 12 × 3 = 12 × [tex]\frac{5}{6}[/tex], that is
9x + 36 = 10 ← equation without fractions
could someone help with the question in the picture, thanks
Answer:
Step-by-step explanation:
a. The lowest temperature in Alaska, -62° C, was recorded on
January 23, 1971 at Prospect Creek Camp. Use the formula to
convert the record temperature to Fahrenheit.
Answer: -79.6°F
Formula
(-62°C × 9/5) + 32 = -79.6°F
Answer:
Step-by-step explanation:
The answer is the -558.9
gcf of 14, 49, and 7 pls help
Answer:
GCF(14, 49, 7) = 7Step-by-step explanation:
14 = (2)(7)
49 = (7)(7)
7 = (7)(1)
GCF(14, 49, 7) = 7
A carpenter is building a ramp, as shown in the diagram.
What is mt?
A. 28º
B. 62º
C. 90º
D. 152º
Answer:
B. 62°
Step-by-step explanation:
According to the Supplementary Angles Theorem, in this case, ∠s and 152° form a straight angle, so you use the Supplementary Angles Theorem:
-152° + 180 = 28°; 28° = m∠s
Then, use the Triangular Interior Angles Theorem to find the m∠t:
28° + 90° = 118°
↑
∠s
-118° + 180° = 62°; 62° = m∠t
I am joyous to assist you anytime.
Answer: Option 'b' is correct.
Step-by-step explanation:
Since we have given that
Measure of exterior angle = 152°
and measure of one opposite interior angle = 90°
Measure of another opposite interior angle be 't'.
As we know that
Sum of interior angle is equal to exterior angle.
[tex]90^\circ+t=152^\circ\\\\t=152^\circ-90^\circ\\\\t=62^\circ[/tex]
Hence, the measure of t is 62°.
Therefore, Option 'b' is correct.
The formula for volume of a rectangular prism is V= l, w, h,. Study the figure shown here. How many cubic units is it?
Answer:
12 cubic units
Step-by-step explanation:
Each square has a length of 1 unit (2units/2 squares = 1unit), therefore since the height of the prism is made up of 3 squares, its length is 3 units.
Using the equation
V = l x w x h
V = 2 x 2 x 3
V = 12 cubic units
the question is 5/7 divided by 8/12
Answer:
1 1/14
Step-by-step explanation:
To divide by a fraction, multiply by the reciprocal of that fraction
5/7 x 12/8
Reduce the fraction with 4
5/7 x 3/2
Multiply the fractions
To multiply the fractions, multiply the numerators and denominators separately
15/14
Alternative form is
1 1/14
Answer: 15/14 or 1 1/14
Step-by-step explanation:
Match the simplified expression with the correct problem.
3/4 (8x + 16)
2x - 5x + 5 - 4
x + x + x +3 + 5 - 2
6x - 7 + 3x + 5
3 + 2(2x + 5)
Answer: 3/4 (8x + 16) simplified expression is 6x + 12
2x - 5x + 5 - 4 simplified expression is -3x + 1
x + x + x +3 + 5 - 2 simplified expression is 3x + 6
6x - 7 + 3x + 5 simplified expression is 9x - 2
3 + 2(2x + 5) simplified expression is 4x + 13
Step-by-step explanation:
3/4 (8x + 16) in the example the 3 is multiplying and the 4 is dividing,
so you can start with multiplication, multiply the 3 for each value into the parenthesis after that you can place 4 as the divisor of this equation
(3 * 8x + 3 * 16) / 4
after we perform this equation the product is the following
(24x + 48) / 4
after this step you can divide the each value into the parenthesis between 4, this process give us separate equations.
(24x/ 4) + (48/4)
if you proceed with the division of each value we will find the last equation.
(24x/ 4) = 6x
(48/4) = 12
then the simplified expression is 6x + 12.
2x - 5x + 5 - 4, with this case you can resolve the equation with the similar values, for example, you can start with the values that has the x, and after that proceed with the simple values.
2x - 5x = -3x
5 - 4 = 1
after we resolve this, you only need placed the values with its sign in one equation then the simplified expression is -3x + 1.
x + x + x +3 + 5 - 2, in this example you can start with the sum of x, and after that proceed with sum of the simple values.
x + x + x = 3x
3 + 5 - 2 = 6
after that we place the values in one expression , then the simplified expression is 3x + 6.
6x - 7 + 3x + 5, in this equation we can star with the similar values, the values with x and after that the simple values
6x + 3x = 9x
-7 + 5 = -2 ( as the 7 is bigger than 5 the result get value of the biggest number.
after you only need to place the values in one equation, then the simplified expression is 9x - 2.
3 + 2(2x + 5), with this example you can start with the product of 2 with the values into the parenthesis.
2 * (2x + 5) the 2 is passing to multiply each value into the parenthesis.
2 * 2x + 2 * 5
4x + 10
after that we can place the result of this product in the first equation
3 + 4x + 10
after that you only need to sum the similar values and we get that the simplified expression is 13 + 4x
Final answer:
Explanation of matching simplified expressions to problems in a math question that is option D is correct
Explanation:
Match the simplified expression with the correct problem:
3/4(8x + 16) matches with 6x - 7 + 3x + 5
2x - 5x + 5 - 4 matches with x + x + x + 3 + 5 - 2
x + x + x + 3 + 5 - 2 matches with 3 + 2(2x + 5)
Solve for b.
2|b| = 2
Write your answers as integers or as proper or improper fractions in simplest form.
b = or b =
2|b| = 2
2b= 2
divide by 2 to get b, by itself
2b/2= 2/2
b=1
2|b| =- 2
2b= -2
2b/2= -2/2
b= -1
Answer:
b= 1, b= -1
I need help I don’t understand this at all
Answer:
all work is pictured/shown
What is the mistake?
3a+4b=7ab
Answer:
You cannot add like terms like that.
Step-by-step explanation:
The terms are supposed to be added together, by combining them like that you are multiplying them together.
The square root of 60 + n and the square root of 2n +28. What is the smallest natural number that could be.
Answer:
If i understood correctly n = 4
Step-by-step explanation:
You are looking for the smallest n that gives a result to the square root so you have to try known squares.
Since you have 60+n, you have to start with 64, 81, 100, etc
First try with 64 means n equals 4
Then you go for the next expresion and replace 4:
2(4) + 28 = 36 which is 6*6
So thats your answer
Final answer:
The smallest natural number that could be the square root of (60 + n) and (2n + 28) is 4.
Explanation:
The smallest natural number that could be √(60 + n) and √(2n + 28) is 8. To find this, we need to solve the equations:
√(60 + n) = 8 and √(2n + 28) = 8.
Squaring both sides of each equation, we get:
60 + n = 64 and 2n + 28 = 64.
Solving these equations, we find:
n = 4 and n = 18.
Since we are looking for the smallest natural number, the answer is 4.
Find the value of a for which the solution of the inequality is all real numbers.
3x+8+2ax≥3ax−4a
How do I solve for a and what does a stand for please help meeeeeee.
Answer:
[tex]a=3,\text{ then } x\in(-\infty,\infty)\\ \\a\in(-\infty,3),\text{ then }x\in \left[\dfrac{-4a-8}{3-a},\infty\right)\\ \\a\in(3,\infty),\text{ then }x\in \left(-\infty, \dfrac{-4a-8}{3-a}\right][/tex]
Step-by-step explanation:
In the inequality
[tex]3x+8+2ax\ge 3ax-4a\ \ \ (1)[/tex]
a is an arbitrary real number.
Separate the terms with x into left side and the terms without x in the right side:
[tex]3x+2ax-3ax\ge -4a-8\\ \\3x-ax\ge -4a-8\\ \\(3-a)x\ge -4a-8\ \ \ (2)[/tex]
First, look at the leading coefficient at x. If this coefficient is equal to 0 (when [tex]a=3[/tex]), then the inequality is
[tex]0\ge -4a-8\\ \\0\ge -12-8\ [\text{Substituted }a=3]\\ \\0\ge -20[/tex]
This is true inequality for all x, so at [tex]a=3,[/tex] the inequality (1) has the solution [tex]x\in (-\infty,\infty)[/tex]
Now, if the leading coefficient
[tex]3-a>0\\ \\a<3,[/tex]
then we can divide the inequality (2) by this positive number [tex]3-a[/tex] and get
[tex]x\ge \dfrac{-4a-8}{3-a}[/tex]
If the leading coefficient
[tex]3-a<0\\ \\a>3,[/tex]
then we can divide the inequality (2) by this negative number [tex]3-a[/tex] and get
[tex]x\le \dfrac{-4a-8}{3-a}[/tex]
So, the answer is
[tex]a=3,\text{ then } x\in(-\infty,\infty)\\ \\a\in(-\infty,3),\text{ then }x\in \left[\dfrac{-4a-8}{3-a},\infty\right)\\ \\a\in(3,\infty),\text{ then }x\in \left(-\infty, \dfrac{-4a-8}{3-a}\right][/tex]